Clinical approach to the treatment of metastatic skin melanoma. Сase study - Dronov, O. I.; Roshchina, L. O.; Bakunets, Y. P.; Levchenko, L. V.; Nahrebetskyi, V. I. (General Surgery, 2025)
Melanoma is an aggressive disease that accounts for approximately 75% of skin cancer‑related deaths. The primary objectives of surgery in metastatic disease are symptom relief and debulking. As effective systemic treatment prolongs survival in a patient population with advanced disease, the role of local palliative therapy potentially increases. When considering palliative surgery, it is crucial to weigh the potential risks of surgical complications against the burden caused by the symptomatic lesions. We present a case report of melanoma TхNхM1c metastasis to the skin in the right supraclavicular area with disintegration and bleeding, metastatic lesions in the cervical, axillary, and subpectoral lymph nodes bilaterally, and metastatic lesions in the left adrenal gland, stage IV. The patient was urgently hospitalized with manifestations of diffuse bleeding associated with tumor disintegration. According to the treatment history, the patient has been receiving targeted chemo‑immunotherapy since 2022. The pain syndrome intensified, and periodic episodes of bleeding from the tumor were observed. Сytoreductive surgery tactics were discussed by the multidisciplinary team and agreed upon with the patient. Тhe patient insisted on removing the tumor despite the risks of the operation. This clinical study deals with a controversial, yet clinically required, palliative care method for preserving and improving the quality of life with this diagnosis. This case highlights the aggressive nature of generalized melanosis, characterized by a rapid clinical course and limited response to traditional targeted chemo‑immunotherapy. The difficulties encountered in the diagnosis and treatment of this aggressive form of metastatic melanoma underscore the need for early detection, tailored therapeutic approaches, and ongoing research efforts to improve treatment outcomes in such cases.